AKTIVITAS ANTIMIKROBA EKSTRAK ETANOL BATANG WOLE WOE TERHADAP MIKROBA PATOGEN MENGGUNAKAN DIFUSI AGAR - Fitriana Fitriana; Sitti Amirah; Safriani Rahman; Sukmawati Sukmawati (Fakultas Farmasi UMI, 2023)
Infectious diseases can be caused by the entry of microorganisms such as bacteria, fungi, parasites, and viruses that can cause diseases in humans. One of the plants used empirically by the Weda community in Central Halmahera is the stem part of the wole woe plant. The aim of this study was to determine the antimicrobial activity of the ethanol extract of wole woe stems against pathogenic microbes such as Propionibacterium acnes, Escherichia coli, Salmonella thypi, Shigella dysentriae, Vibrio cholerae, and Candida albicans. This study used the agar diffusion method with various concentrations of 2.5%, 5%, and 10%, and positive controls for bacteria with chloramphenicol, positive controls for fungi with nystatin, and DMSO as a negative control. Based on the average diameter of the inhibition zone obtained, the test microbes were classified into the medium-strong category because they had an inhibition zone diameter ranging from 9 mm to 13 mm. The positive control for chloramphenicol for bacteria was classified into the very strong category because it had an inhibition zone diameter of >20 mm, while the positive control for nystatin for fungi was classified into the strong category because it had an inhibition zone diameter of >10 mm. Based on these tests, it can be concluded that the ethanol extract of wole woe stems has antimicrobial activity